Sense, Essence and Essentiality of Performance Management System - An Analysis - Panda, Sitansu; Pradhan, Prasanna Kumar (PSG Institute of Management, 2017)
Performance Management System (PMS) is important for organizations. The essence of PMS should be clearly understood by the employees working with different responsibilities. Clarity, acceptability, space for incorporating modifications, scope for employee development and similar features should be there with PMS. In this study, association of PMS with Job Satisfaction (JS) has been explored which reveals a positive and significant association. The essentiality of PMS viewed by the employees for the development of employees as well as for the organization is also the finding by the researchers.